Time Series Forecasting Model of Future Spectrum Demands for Mobile Broadband Networks in Malaysia, Turkey, And Oman - Ibraheem Shayea; Abdulraqeb Alhammadi; Ayman A. El-Saleh; Wan Haslina Hassan; Mustafa Ergen; Hafizal Mohamad (Elsevier, 2024)
Indexed by WOS/Scopus/ERA